Could Dietary Supplementation with Different Sources of N-3 Polyunsaturated Fatty Acids Modify the Rabbit Gut Microbiota? - Giulio Curone; Filippo Biscarini; Elisa Cotozzolo; Laura Menchetti; Alessandro Dal Bosco; Federica Riva; Paola Cremonesi; Stella Agradi; Simona Mattioli; Bianca Castiglioni; Alessia Di Giancamillo; Alice Cartoni Mancinelli; et al. (MDPI AG, 2022)
The present study evaluated the effects of feed supplemented with two dietary sources of n-3 polyunsaturated fatty acids (PUFAs; fish oil and extruded flaxseed) on the gut microbiota, caecal fermentations, gastrointestinal histology, and histochemistry in rabbits. Fifteen male New Zealand White rabbits were divided into three groups (n = 5/group) and fed with different diets from weaning (35 days of age) until slaughtering (90 days of age): C group, fed with a commercial diet; F group, supplemented with 10% of extruded flaxseed; and O group, supplemented with 3.5% of fish oil. At slaughter, the content of the stomach, duodenum, jejunum, ileum, caecum, and colon was collected and analyzed by Next Generation 16S rRNA gene sequencing. Tissue samples of the same tracts were evaluated with histological and histochemical analysis. Ammonia and lactic acid in the caecum were also quantified. Twenty-nine operational taxonomic units (OTUs) were significantly different between groups. Groups receiving n-3 PUFAs supplementation showed an increase in Bacteroidetes and Lachnospiraceae in several gastrointestinal tracts, while Bacilli abundance, as well as Firmicutes/Bacteroidetes ratio, were reduced compared to the control group (for all p < 0.05). Caecal ammonia was lower in the F than C group (p < 0.032), whereas no difference was found for lactic acid. Finally, histological evaluations revealed a mild hemorrhagic infiltration and vessels ectasia in the stomach mucosa of both F and O groups, but no effect of nutritional treatment was evidenced by the histochemical analyses. In conclusion, n-3 PUFAs supplementation could modify the rabbit gut microbiota and fermentation. The increase in beneficial bacterial populations may, at least partially, explain the positive effects of n-3 PUFAs diet supplementation on human and animals' health, although the appropriate dosage should be established.